Foreign direct investment and institutional stability: who drives whom? - Mahmood, Nihal (2019)
Purpose – The purpose of this paper is to examine the relationship between foreign direct investment (FDI) flows and institutional stability. The focus country is Canada. It is one of the few countries where the economy remained relatively stable compared to other economies during the Global Financial Crisis. It is crucial for Canada to determine the optimal level of institutional development to attract more FDI and sustain the sound financial stability in future. Design/methodology/approach – This study uses the auto-regressive distributive lag (ARDL) approach to understand the relationship between FDI and institutional stability along with other controlled variables for instance gross national product inflation and exports. Findings – The key finding of this work is that FDI and institutional stability are cointegrated in the long run. The error correction model of ARDL shed light on institutional stability being an exogenous variable and FDI is an endogenous variable. Institutional stability affects FDI as it is exogenous. The findings will help policymakers to implement policies to strengthen the institution’s settings and this in turn will attract more investment. Originality/value – Based on previous theoretical and empirical literature most of the research points to FDI positively affect institutional stability. In some cases the relationship does not always hold true. This study will fix the gap in the literature by investigating the relationship between FDI and institutional stability of Canada.